MULTILEVEL GOVERNANCE DAN PEMBENTUKAN KEBIJAKAN LINGKUNGAN DI UNI EROPA (STUDI KASUS: EUROPEAN UNION TIMBER REGULATION 2005-2015) - Sari Oktaviani, (2020)
This research explores EU environmental policies to halt illegal logging and its associated trade. Despite being promising, the bilateral FLEGT-VPA agreement turns out to have limitations. Eventually, the EU is set to draft a new regulation that is the European Union Timber Regulation (EUTR). This study aims to describe in detail the process of EUTR policymaking through multilevel governance and multilateral negotiation perspectives. From the multilevel governance, this paper emphasizes the four stages of EUTR policymaking: (1) policy initiation, (2) decision making, (3) implementation, (4) and adjudication. The enactment of EUTR involves multi-actors activity at each stage of its policy making. Unanimity becomes a challenge to formally adopt the EUTR during decision making as the EU bodies share opposite intentions, at the same time NGO and civil society seek to influence by promoting their interests, therefore prolonging the heated debate at the EU level. It takes trilogue meetings, which is considered as a form of multilateral negotiation, among the Parliament, the Council, and the Commission to finally reach a compromise agreement and send a clear signal that the EUTR measures stand on unanimous. To deliver relevant analysis, qualitative research and process tracing methods are applied in this study, and data sources are obtained from library research.